Job search during the covid-19 crisis - Lena Hensvik; Thomas Le Barbanchon; Roland Rathelot (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
This paper measures the job-search responses to the COVID-19 pandemic using realtime data on vacancy postings and job ad views on Sweden's largest online job board. First, new vacancy postings drop by 40%, similar to the US. Second, job seekers respond by searching less intensively, to the extent that effective labour market tightness increases during the first three months after the COVID outbreak. Third, they redirect their search towards less severely hit occupations, beyond what changes in vacancies would predict. Overall, these job search responses have the potential to amplify the labour demand shock.
Keywords: J22; J23; J21; J62; J63; J64; E24; 330; coronavirus; search intensity; search direction; labour demand shock; job vacancies; online job board